Pests and diseases in a changing climate a major challenge for Finnish crop production - Hakala, Kaija; Hannukkala, Asko O.; Huusela-Veistola, Erja; Jalli, Marja; Peltonen-Sainio, Pirjo (Agricultural and Food Science, 2011)
A longer growing season and higher accumulated effective temperature sum (ETS) will improve crop production potential in Finland. The production potential of new or at present underutilised crops (e.g. maize (Zea mays L.), oilseed rape (Brassica napus L.), lucerne (Medicago sativa L.)) will improve and it will be possible to grow more productive varieties of the currently grown crops (spring wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), oats (Avena sativa L.)). Also cultivation of autumn sown crops could increase if winters become milder and shorter, promoting overwintering success. Climatic conditions may on the other hand become restrictive in many ways. For example, early season droughts could intensify because of higher temperatures and consequent higher evaporation rates. Current low winter temperatures and short growing season help restrict the development and spread of pests and pathogens, but this could change in the future. Longer growing seasons, warmer autumns and milder winters may initiate new problems with higher occurrences of weeds, pests and pathogens, including new types of viruses and virus vectors. Anoxia of overwintering crops caused by ice encasement, and physical damage caused by freezing and melting of water over the fields may also increase. In this study we identify the most likely changes in crop species and varieties in Finland and the pest and pathogen species that are most likely to create production problems as a result of climate change during this century.;